Is there a rural/urban gap in the quality of HIV care for treatment-naïve HIV-positive individuals initiating antiretroviral therapy in British Columbia?. Issue 10 (3rd October 2017) - MacKenzie, Lauren J.; Hull, Mark W.; Samji, Hasina; Lima, Viviane D.; Yip, Benita; Zhang, Wendy; Lourenço, Lillian; Colley, Guillaume; Hogg, Robert S.; Montaner, Julio S. G.
ABSTRACT: Rurally located people living with HIV (PLWH) face unique challenges associated with remoteness that may negatively affect their HIV care outcomes. The Programmatic Compliance Score (PCS) has been used previously as a quality of care metric, and is predictive of mortality for treatment-naïve individuals initiating combination antiretroviral therapy (cART). This study looked at whether the rurality of PLWH impacted their PCS. PCS was calculated for PLWH (≥19 years old) initiating cART in British Columbia between 2000 and 2013. Rurality was determined at the time of cART initiation using two methodologies: (1) a categorical postal code method; and (2) the General Practice Rurality Index (GPRI), a score representing an individual's degree of rurality. Ordinal logistic regression modeling was used to assess the relationship between rurality and PCS. Among 4616 PLWH with an evaluable PCS, 176 were classified as rural and 3512 as urban (928 had an unknown postal code). After adjusting for age, sex, hepatitis C status, Indigenous ancestry, and year of cART initiation, categorical rurality was not associated with a worse PCS (adjusted odds ratio (AOR) 1.04; 95% CI: 0.77–1.39). However, an increasing degree of rurality was associated with a worse PCS (AOR (per 10 increase in GPRI) 1.13; 95% CI: 1.06–1.20). Given that a poor PCS has been shown to be predictive of all-cause mortality for individuals initiating cART, strategies to improve access to HIV care for rural individuals should be evaluated.